2007
DOI: 10.1111/j.1365-2934.2006.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between multidimensional leadership and burnout among nursing staff

Abstract: The relation between leadership and burnout is complex, affected by situational factors of leadership and the ambiguous nature of burnout. Nurses of various ages, at different stages of career development and participating in different work tasks require different kinds of leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 22 publications
9
108
0
2
Order By: Relevance
“…This lends support to both Hypothesis 1 and existing research [33,36,55]. Further, destructive leader behavior also added significantly to the prediction of work engagement (4.7%), indicating that exposure to destructive leadership is associated with a lower degree of work engagement in the respondents and supporting our Hypothesis 2.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This lends support to both Hypothesis 1 and existing research [33,36,55]. Further, destructive leader behavior also added significantly to the prediction of work engagement (4.7%), indicating that exposure to destructive leadership is associated with a lower degree of work engagement in the respondents and supporting our Hypothesis 2.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have supported a positive relationship between destructive leadership and burnout, mostly in health care contexts. Kanste et al found that the experience of laissez-faire leadership in the health care sector correlated positively with all the three dimensions of burnout, while Hetland et al found destructive leadership to increase the risk of burnout among subordinates [33,36]. However, the influence of destructive leadership on burnout in a military context requires further exploration.…”
Section: Burnoutmentioning
confidence: 99%
“…Transformational leadership has been found to be associated with low burnout, or specifically, low exhaustion in employees (e.g. Corrigan, Diwan, Campion, & Rashid, 2002;Hetland, Sandal, & Johnsen, 2007;Kanste, Kyngäs, & Nikkilä, 2007). More recently, positive associations between transformational leadership and employee work engagement have also been reported (Ghadi et al, 2013;Salanova, Lorente, Chambel, & Martínez, 2011;Tims et al, 2011).…”
Section: Leadership Behaviours In Relation To Work Engagement and Burmentioning
confidence: 84%
“…The majority of leadership styles is evaluated unambiguously in the context of occupational burnout. Transformational, authentic, participative, or supportive leadership styles are related to lower probability of occupational burnout while transactional and laissez-faire leadership styles are related to higher probability of occupational burnout (Yuan, & Lee, 2011;Gill, Flaschner, & Shachar, 2006;Russell, 2014;Laschinger, Wong, & Grau, 2012;Zehir, Ertosun, Zehir, & Müceldili, 2011;Zopiatis, & Constanti, 2010;Kanste et al, 2007). Still the relationship between ethical leadership and burnout is not clear.…”
Section: Introductionmentioning
confidence: 94%
“…Still the relationship between ethical leadership and burnout is not clear. Authors state that issues of ethical leadership in the context of burnout need further and more deep investigations (Kanste, Kyngas, & Nikkila, 2007;Cremer, 2015).…”
Section: Introductionmentioning
confidence: 99%